Evaluation of Coffee Mistletoe Leaf Ethanol Extract on Burn Healing Activity on White Male Rat - M. Rifqi Efendi; Diah Riski Gusti; Annisa Dhita Syahrial; Mesa Sukmadani Rusdi (Journal of Pharmaceutical and Sciences, 2023)
Burns are injuries that can be caused by heat (fire, hot liquids/fats, hot vapors), radiation, electricity, or chemicals. Coffee mistletoe leaves (Loranthus ferruginous Roxb) are one type of plant that contains secondary metabolite compounds, such as flavonoids, tannins, saponins, alkaloids, and phenolics, which play a role in the burn healing effects. This research was conducted using an experimental research method with a Completely Randomized Design (CRD) and a post-test only control group design approach. A total of 25 rats were divided into five treatment groups for the study. The groups included a positive control group treated with Bioplacenton gel, a negative control group treated with yellow vaseline, and three experimental groups treated with different concentrations of ethanol extract of coffee mistletoe leaves. The concentrations used were 5% (P1), 10% (P2), and 15% (P3). The burn healing activity and hydroxyproline content were observed as outcome measures. The data were presented as mean ± SD and analyzed using one-way ANOVA. Subsequently, Duncan's multiple rank test was performed to determine any significant differences. A significance level of p<0.05 was considered to define statistically significant results. The results of the study showed that ethanol extract of coffee mistletoe leaves has an effect as a burn treatment, with the best concentration found at 15% concentration, which had a healing percentage of 62.5%, although its effectiveness did not exceed that of the positive control group (72,48%). The hydroxyproline content of the coffee mistletoe leaf extract group demonstrated significant difference when compared to control negative groups, especially P1 group (53.62±6.52 μg/mL), and statistically not different with positive control (64.34 ±6.02 μg/mL). For the P2 and P3 groups, the hydroxyproline content were increased but did not reach significant value. Wound-healing activity owing to its richness in various effective chemical compounds present in the extract such as phenolics, saponin, flavonoid and alkaloid. Further investigation is necessary to identify and understand these additional components and their mechanisms of action in the healing process.